2004
DOI: 10.1891/vivi.19.2.239.64102
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Reactions of Bystanders and Victims to Repetitive Abuse Experiences

Abstract: This study investigated psychological distress as measured by the Impact of Events Scale-Revised and physiological reactivity as measured by skin conductance and heart rate in bystanders as compared to direct victims of prevalent forms of repetitive abuse (e.g., bullying). Participants (N = 77) were interviewed twice: once to recall witnessing another person be abused repeatedly over time, and again to recall similar experiences as a victim. Present levels for bystander and victim distress were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 56 publications
3
50
2
1
Order By: Relevance
“…This set of repetitive stressful life events leads to a severe psychological discomfort including strong feeling of fear or even hopelessness [5]. In line with this, earlier studies have also shown that symptoms found among targets of workplace bullying can be compatible with that of post-traumatic stress [1], and numerous studies confirm the associations between workplace bullying and severe mental health problems including posttraumatic stress symptoms [2,53]. Such findings, and not Yet, it also shows that experiences and outcomes of workplace bullying may be hidden within other health related problems at work or in one's daily life or personal habits and characteristics.…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 71%
See 2 more Smart Citations
“…This set of repetitive stressful life events leads to a severe psychological discomfort including strong feeling of fear or even hopelessness [5]. In line with this, earlier studies have also shown that symptoms found among targets of workplace bullying can be compatible with that of post-traumatic stress [1], and numerous studies confirm the associations between workplace bullying and severe mental health problems including posttraumatic stress symptoms [2,53]. Such findings, and not Yet, it also shows that experiences and outcomes of workplace bullying may be hidden within other health related problems at work or in one's daily life or personal habits and characteristics.…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 71%
“…Other studies have shown that post-traumatic stress symptoms are prevalent in 63-76% of all victims of severe bullying [1,53]. A Swedish study based on patients at a rehabilitation clinic for victims of workplace bullying showed that 59 out of 64 patients were diagnosed with PTSD [13].…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…35 Most of the costs to bullying, however, are borne by the victims and other children who witness the harassment but feel powerless against it. 36 In fact, the 3 most robust sources of stress that negatively impact health stem from power differentials: low social status, lack of friends, and stress early in life. 20 This scenario is exactly the plight of the bullied child.…”
Section: Dominance In a Child's World: Bullyingmentioning
confidence: 99%
“…Bystanders who witness bullying may experience mental health consequences (eg, distress) as well. 36,37 The American Academy of Pediatrics and other major professional organizations have issued policy statements recognizing bullying as a serious medical and public health issue that pediatricians and other clinicians should address jointly with parents, educators, and community organizations. [38][39][40][41][42][43][44] Professional organizations recommend that clinicians take concrete steps to respond to bullying.…”
mentioning
confidence: 99%